The development of insurance management system for Insurans Hayat dan Am (IHA) Agency / Nursabrina Abu Bakar - Abu Bakar, Nursabrina (2017)
Insurance Management System (IMS) is the system that developed to assist the admin and staff to manage data entry, calculate estimation amount of claim and notify customer by Short Messaging Service (SMS). The aim of this project is to develop the Insurance Management System for Insurans Hayat dan Am (IHA) Agency. Next, the objectives of this project are to gather and analyzed requirements from IHA Agency, to design an IMS and to develop an IMS. Currently, the agency has faced problem to manage data entry, not able to answer customer’s question about the estimation amount of claim and send message to customer manually. This system may able to reduce the current problem of the insurance management. Mainly, this system is focused on calculate estimation amount of claim. Other than that, this system also able to generate SMS to alert customer about their payment. Methodology that applied for this project is Waterfall Model. There are three (3) phases involved in this project. The first phase is gathered and analyzed the requirements. Meanwhile, second phase is system design and last phase is system development. The programming language that used for this system is Java language while SQL Developer is used to store the data of the system. This system are benefits to the admin and staff as it assists in insurance management. The future enhancement of this system is to connect with any insurance company and enlarge the scope of the system. In nutshell, IMS was developed to reduce the problem of the current insurance management with able to manage data entry, calculate estimation amount of claim and notify customer by SMS.